Upaya Preventif dan Represif dalam Penanggulangan Kebocoran Data Pada Penyelenggaraan Pinjaman Online - Gunawan, Imam (Officium Notarium, 2024)
Fintech as a financial service provides convenience for the community, especially fintech lending infrastructure. The discourse on fintech lending, also known as pinjol, has had a very positive effect on society. However, the increasing number of data leak cases has resulted in the existence of fintech lending being misused by unscrupulous individuals. The aim of this research is for readers to learn about preventive steps to overcome data leaks, the validity of transactions, and the resulting legal consequences. The author provides several repressive measures as a legal umbrella against data leaks in the provision of online loans based on statutory regulations and initiates prevention efforts through the application of biometric technology. This research uses qualitative data analysis techniques with a normative research type and also uses two approaches, namely a statutory approach and a conceptual approach. The legal materials in this research use primary and secondary legal materials. The correlation between the statutory approach and primary law is to examine the regulations determined by the online loan administration system, which is currently widespread in Indonesia. Online loans are meant to be illegal online loans, which are problematic because of the ease of submitting funds, which results in data leaks. The emergence of cases in the implementation of online loans shows weak data protection and the ease of loan application and authentication. Therefore, there is a need for further efforts to handle cases involving the implementation of online loans. Repressive efforts with the presence of statutory regulations such as the Civil Code, ITE Law, PDP Law, P2SK Law, and PJOK Number 10/POJK.05/2022 concerning Joint-Based Funding Services Information Technology as a legal protection.Keywords: Biometric Technology; Online Treatment; Leaks Data; Data Protection AbstrakFintech sebagai layanan keuangan memberikan kemudahan bagi masyarakat khususnya fintech lending dalam prasarana peminjaman. Diskursus fintech lending atau dikenal pinjol sangat memberikan efek positif bagi masyarakat. Namun, maraknya kasus kebocoran data mengakibatkan eksistensi fintech lending disalahgunakan oleh para oknum. Tujuan penelitian ini agar para pembaca mengetahui mengenai langkah preventif guna menanggulangi kebocoran data, keabsahan transaksi, serta akibat hukum yang ditimbulkan. Penulis memberikan beberapa upaya represif sebagai payung hukum terhadap kebocoran data pada penyelenggaraan pinjaman online berbasis peraturan perundang-undangan dan menggagas upaya pencegahan melalui penerapan biometric technology. Penelitian ini menggunakan teknik analisis data kualitatif dengan jenis penelitian normatif serta menggunakan 2 pendekatan yaitu pendekatan perundang-undangan (statue approach) dan pendekatan konseptual. Adapun bahan hukum pada penelitian ini menggunakan bahan hukum primer dan sekunder. Korelasi pendekatan undang-undang dengan hukum primer adalah untuk mengkaji regulasi yang ditentukan pada sistem penyelenggaraan pinjaman online yang sedang marak terjadi di Indonesia. Pinjaman online dimaksudkan adalah pinjaman online ilegal yang menjadi problematika karena kemudahan pengajuan pengajuan dana yang berakibat pada kebocoran data. Lahirnya kasus-kasus dalam penyelenggaraan pinjaman online menunjukkan lemahnya perlindungan data serta kemudahan pengajuan pinjaman dan autentifikasinya. Maka dari itu perlu adanya upaya lebih lanjut untuk menangani kasus pada penyelenggaraan pinjaman online.Upaya represif dengan hadirnya peraturan perundang-undangan seperti KUHPer, UU ITE, UU PDP, UU P2SK, maupun PJOK Nomor 10/POJK.05/2022 tentang Layanan Pendanaan Bersama Berbasis Teknologi Informasi sebagai payung hukum.Kata Kunci: Biometric Technology; Pinjaman Online; Kebocoran Data; Perlindungan Data